1995
DOI: 10.1093/carcin/16.5.993
|View full text |Cite
|
Sign up to set email alerts
|

Gender comparisons in human lung cancer: analysis of p53 mutations, anti-p53 serum antibodies and C-erbB-2 expression

Abstract: Little is known about the molecular mechanisms of lung carcinogenesis in women. We initiated an investigation of the role of gender in pulmonary carcinogenesis by analysis of p53 mutations, immunohistochemistry, serum antibodies and c-erbB-2 expression in a series of 63 male and 44 female lung cancer patients whose tumors were resected at the Mayo Clinic between 1991 and 1992. There were 102 smokers and 5 never smoked. Adenocarcinoma was the more frequent histological type in women (62%) than in men (41%). Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 0 publications
7
44
0
Order By: Relevance
“…10). Consistent with these results, in previous studies that reported a higher frequency of G:C-to-T:A mutations in women, gender differences were not statistically significant (8,5). Women smoked fewer cigarettes than men in these studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…10). Consistent with these results, in previous studies that reported a higher frequency of G:C-to-T:A mutations in women, gender differences were not statistically significant (8,5). Women smoked fewer cigarettes than men in these studies.…”
Section: Discussionsupporting
confidence: 89%
“…Differences in type of mutations in TP53 were estimated by Fisher's exact tests when expected counts were V5, or m 2 tests. Using two-sided tests, a of 0.05, and the frequency of G:C-to-T:A mutations in TP53 in previous studies of 25% or 27% in men and 40% in women, our study had 89% or 78% power to detect a statistical difference (8,5). Differences in pack-years of smoking were compared using t-tests.…”
Section: Methodsmentioning
confidence: 99%
“…Sex-specific differences have also been observed for associations between EGFR mutations and the HLA-A2(þ) allele. 24 In addition, p53 transversion mutations 25 and insertion/deletion mutations 26 are more frequent in females. Various carcinogens originated from environmental exposures or endogenous processes constantly threaten DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies of cigarette smoke have shown that, at the same exposure level, women differ in their resistance to lung damage compared to men. Xu et al (94) report that adverse effects of smoking on pulmonary function are greater in women than in men, and other studies indicate sex differences in lung dysfunction, and in genetic and biochemical alterations in lung cancer (95)(96)(97).…”
Section: Analysis Of Variability and Susceptibilitymentioning
confidence: 99%